GE_GERICHTE P/4078/2017 vom 12. Dezember 2018 - GE Cour de justice (2018)
USURE(DROIT PÉNAL) ; TRAVAIL AU NOIR ; RÉMUNÉRATION ABUSIVE | LEtr.116.al1.leta; LEtr.117.al1; LAVS.157.al1; CPP.147.al1; CP.47; CP.49; CP.42.al4; CP.106; CPP.433.al1; CPP.1; CPP.428.al3; CPP.429; CPP.442.al4; CPP.433.al1